2005
DOI: 10.1242/dev.01928
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of dendrite pruning inDrosophila: insights from in vivo time-lapse of remodeling dendritic arborizing sensory neurons

Abstract: Regressive events that refine exuberant or inaccurate connections are critical in neuronal development. We used multi-photon, time-lapse imaging to examine how dendrites of Drosophila dendritic arborizing (da) sensory neurons are eliminated during early metamorphosis, and how intrinsic and extrinsic cellular mechanisms control this deconstruction. Removal of the larval dendritic arbor involves two mechanisms: local degeneration and branch retraction. In local degeneration, major branch severing events entail f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
316
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(326 citation statements)
references
References 48 publications
9
316
1
Order By: Relevance
“…In addition, marking the microtubules and membranes of ddaC neurons by antibody double staining at 5 h APF, we found that the dendritic membranes were still connected to the soma in some regions of proximal dendrites where the microtubules were already disrupted or absent (Fig. 3 G-I) (12). Thus, the microtubule breakage in the proximal dendrites appears to precede the physical separation of dendrite membrane from the cell body.…”
Section: Localized Breakage Of Microtubule and Actin Cytoskeletons Inmentioning
confidence: 76%
See 4 more Smart Citations
“…In addition, marking the microtubules and membranes of ddaC neurons by antibody double staining at 5 h APF, we found that the dendritic membranes were still connected to the soma in some regions of proximal dendrites where the microtubules were already disrupted or absent (Fig. 3 G-I) (12). Thus, the microtubule breakage in the proximal dendrites appears to precede the physical separation of dendrite membrane from the cell body.…”
Section: Localized Breakage Of Microtubule and Actin Cytoskeletons Inmentioning
confidence: 76%
“…Overexpression of dominant negative ecdysone receptor (EcR-DN) efficiently suppressed dendrite pruning in ddaC neurons (12,13), and eliminated any sign of microtubule disruption in the dendrites at 6 h APF (Fig. 3J).…”
Section: Localized Breakage Of Microtubule and Actin Cytoskeletons Inmentioning
confidence: 99%
See 3 more Smart Citations